Managing customer workflow via IDAN's tracking system - Razak, Aqif Haikal; Mohamad Rosman, Mohamad Rahimi; Firdaus, Muhamad Afiq (International Journal of Accounting, Finance and Business, 2026)
Idan’s Track is a web-based customer order tracking system developed for Small and Medium-sized Enterprises (SMEs) in the apparel and printing industry. The system addresses common operational issues such as a lack of order visibility, fragmented communication, and weak workflow traceability. It provides a centralized platform that allows customers to track their orders in real time using QR codes or order IDs, while staff updates progress across eight standardized production stages. Developed using the Waterfall model and implemented with PHP, MySQL, HTML, CSS, and JavaScript, the system improves transparency, accountability, and customer satisfaction. The findings suggest that a structured tracking system can significantly enhance operational efficiency and customer engagement for SMEs